Experimental investigation on mechanical behaviors of PET fabric coated/uncoated PVC for automobile airbags use subjected to uniaxial, biaxial tension and in-plane large shear deformation - Changsheng Wang; Tao Ma (Journal of Engineered Fibers and Fabrics)
PET (Polyethylene Terephthalate) fabric, as one of the airbag materials, has good viscoelasticity and permeability. The surface treatment of airbag fabrics often comes in two types (coated and uncoated) depending on their type and cost. In this study, two fabrics of the automobile airbag material PET was used in the presence and absence of surface coating with PVC (polyvinyl chloride). Three different types of experimental tests including off-axial uniaxial tension, biaxial cyclic loading and picture-frame shear cyclic loading were used depending on the fabric’s load state during the airbag inflatable deployment and folding process. The two materials’ uniaxial tensile modulus and the biaxial tensile modulus were successfully obtained. According to the experimental results of the two materials, the coated material was found to have superior elastic properties than the uncoated material. However, the stress-strain change path was consistent, allowing for a more accurate definition of the material properties of automobile airbag fabric and stronger technical support for the development of automobile airbag safety.